Designing A Cattle Farm Based On Modern Architecture in Banyuwangi Regency - Intan Kusumaningayu; Mochamad Malik Mutafarriki; Darmansjah Tjahja Prakasa (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Banyuwangi Regency is one of the regions with significant potential in the livestock sector, particularly beef cattle, which serve as a major contributor to local meat production. Despite its large cattle population and strategic position as a livestock distribution hub in East Java, existing livestock and cattle trading facilities in Banyuwangi are still predominantly traditional, lacking proper hygiene, efficiency, and compliance with animal welfare and sanitation standards. Problems related to inadequate housing infrastructure, poor health management, limited market access, and insufficient waste treatment remain major constraints that affect the productivity and quality of livestock. This study and design proposal aim to develop a concept for a modern architecture–based cattle farming and trading facility capable of addressing these issues. The design approach integrates four main perspectives: a functional approach to optimize cattle management and trading activities; an ecological architectural approach to ensure environmental sustainability; a socio-economic approach to improve farmer welfare and strengthen the local economy; and a contextual approach that aligns the design with the cultural and climatic characteristics of Banyuwangi. The proposed facility includes modern barns, veterinary health units, hygienic trading areas, educational spaces, feed storage facilities, and an integrated waste-management system. The results indicate that providing standardized, hygienic, and environmentally friendly livestock facilities can improve distribution efficiency, reduce disease risks, and enhance farmer productivity. Moreover, the integration of modern technology and zoning strategies based on animal welfare provides a better environmental quality for both livestock and facility users. Consequently, this design is expected to serve as a sustainable model for cattle farming and trading facilities while strengthening Banyuwangi’s position as a regional livestock agribusiness center.